Shared Rule in Federal Theory and Practice - Mueller, Sean (Oxford University Press, 2024)
This book provides the first-ever in-depth treatment of shared rule, a crucial but so far largely neglected dimension of federalism and multilevel governance. The book discusses shared rule’s conceptual evolution and defines three different meanings commonly ascribed to it: shared rule as horizontal cooperation, centralisation, or bottom-up influence seeking. An original expert survey conducted among 38 federalism scholars in 11 countries is used to measure actual as opposed to merely potential regional government influence over national decisions. Drawing on a wide range of literature, from lobbying and political parties to power sharing and secessionism, the book then investigates the emergence and impact of shared rule thus understood. The evidence presented includes qualitative case studies on Belgium, Canada, Germany, Spain, Switzerland, and the US as well as quantitative, cross-sectional analyses at regional and national level. The book shows that shared rule has the potential to become the holy grail of territorial politics in that it satisfies both those wanting greater unity and uniformity of policy making as well as those desiring greater regional autonomy and recognition of diversity. Building on the conceptual and empirical groundwork laid by the Regional Authority Index, the book thus takes us further and deeper still into the mechanics of territorial contestation, cooperation, and cohesion.